Penilaian Tricuspid Aannular Plain Systolic Excursion (TAPSE) pada Pasien Pra dan Pasca Bedah Pintas Koroner - Wijayanti, Santi; Wati, Erna (ARKAVI [Arsip Kardiovaskular Indonesia), 2016)
ABSTRACT   Coronary heart disease (CHD) is one of cardiovascular diseases caused by constriction of coronary artery, due to either the process of atherosclerosis or spasm or the combination of both. One of the coronary heart disease treatments is Coronary Artery Bypass Grafting (CBAG) surgery. It is an alternative therapy to the patients with constriction in some locations of coronary artery (multi vessel) particularly left main coronary artery. Echocardiography observation is required to be done to the patient before and after CBAG surgery in order to evaluate patient's heart condition. Echocardiography observation can assess both ventricles function, wall segmental motion and heart valves condition and diagnose the presence of pericardial effusion. All the time, the left ventricle function received more attention than the right one. In fact, the impact of CBAG surgery to the right ventricle function is decreasing. The assessment of right ventricle systolic function can be done using Right Ventricular Index of Myocardial Performance (RVMPI) Tricuspid Annular Plain Systolic Excursion (TAPSE), Right Ventricular Fractional Area Change (RVFAC), danTissue Doppler tricuspid lateral annular systolic velocity (S′) parameters. Among those echocardiography observation mentioned, right ventricle systolic function assessment using TAPSE is considered quite accurate, easy, affordable, and safe. Thus, it is commonly sed in daily clinic.   Keywords : Coronary, Systolic, Heart, TAPSE   ABSTRAK   Penyakit Jantung Koroner (PJK) adalah penyakit jantung yang disebabkan karena penyempitan arteri koroner, akibat proses aterosklerosis atau spasme atau kombinasi keduanya. Salah satu penanganan PJK adalah Bedah Pintas Koroner. Bedah pintas koroner merupakan terapi pilihan pada pasien dengan penyempitan di beberapa lokasi arteri koroner (multi vessel), terutama yang menyangkut arteri koroner utama kiri (left main coronary artery). Pada pasien pra dan pasca Bedah Pintas Koroner diperlukan pemeriksaan ekokardiografi untuk mengevaluasi  kondisi jantung pasien. Ekokardiografi dapat melakukan penilaian fungsi kedua ventrikel, gerakan segmental dinding, maupun kondisi katup katup jantung dan adanya efusi perikard. Selama ini fungsi ventrikel kiri lebih mendapat perhatian lebih daripada fungsi ventrikel kanan. Padahal dampak bedah pintas koroner terhadap fungsi ventrikel kanan mengalami penurunan. Penilaian fungsi sistolik ventrikel kanan dapat dilakukan dengan menggunakan parameter Right Ventricular Index of Myocardial Performance (RVMPI), Tricuspid Annular Plain Systolic Excursion (TAPSE), Right Ventricular Fractional Area Change (RVFAC), dan Tissue Doppler tricuspid lateral annular ststolic velocity (S′). Diantara beberapa pemeriksaan ekokardiografi tersebut di atas, penilaian fungsi sistolik ventrikel kanan dengan TAPSE dianggap cukup akurat, mudah, murah dan aman, sehingga banyak dipakai dalam kegiatan klinik sehari-hari.   Kata Kunci : Koroner, Sistolik, Jantung, Tapse